Assessment of rehabilitation needs in patients after COVID-19: Development of the COVID-19-rehabilitation needs survey - Christina Lemhöfer; Christoph Gutenbrunner; Jörg Schiller; Dana Loudovici-Krug; Norman Best; Andrea Bökel; Christian Sturm (Medical Journals Sweden, 2021)
Objective: COVID-19 can result in a broad spectrum of dysfunctions, some of which may persist for long periods, requiring long-term rehabilitation. A comprehensive screening tool is therefore necessary to identify these needs. To date, no data exist on satisfaction with medical and therapeutic interventions for COVID-19 in terms of quality and quantity. The aim of this study is to develop a survey for use with COVID-19 patients during and after the end of the acute phase of the disease. Methods: Following the definition of dimensions by a group of experts, and a literature search, proven survey instruments were searched for suitable items. In addition, specific questions were developed based on symptoms, and answer options were created with regard to to the complexity of the questions. Results: The COVID-19 Rehabilitation Needs Survey (C19-RehabNeS) consists of the established 36-item Short Form Survey (SF-36) together with the newly developed COVID-19-Rehabilitation Needs Questionnaire (C19-RehabNeQ) (11 further dimensions, respectively 57 items). Conclusion: C19-RehabNeS is a comprehensive survey to assess functional limitations and rehabilitation needs during and after infection with SARS-CoV-2 (COVID-19). The strength of this survey is that it combines the assessment of important rehabilitation needs with assessment of satisfaction with the health services, treatment and therapy during the pandemic (C19-RehabNeQ) and assessment of patients' quality of life (SF-36). The C19-RehabNeS survey also enables collection of systematic information on patients with Post-COVID-19 syndrome (Long-COVID-19)